Yeah that is correct so yeah you are right I don’t know any more information that I could give you but I’m pretty sure you just said it right so yeah
From the first equation
6x - y = 1
6x - y - 1 = 0
6x - 1 = y
Substituting we get
4x - 3(6x - 1) = -11
Answer:
x = 8
y = 14
Step-by-step explanation:
2x + 6 = 4x - 10 (Corresponding angles so they're equal)
2x - 4x = -10 - 6
-2x = -16
x = 8
2x + 6 + 13y - 24 = 180 (Supplementary angles so they add up to 180)
2(8) + 6 + 13y - 24 = 180
16 + 6 + 13y - 24 = 180
13y - 2 = 180
13y = 182
y = 14
2(5x^2+2x)+2(3x^2)
10x^2+4x+6x^2
16x^2+4x
D is the correct answer.
Attached you will see the answer (use polynomial division)